Organic matter enrichment model of Permian Capitanian-Changhsingian black shale in the intra-platform basin of Nanpanjiang basin - Zhang, Haiquan; Cao, Junfeng; Lan, Baofeng; Chen, Yi; Zhang, Qian; Men, Yupeng; Feng, Xintao; Yu, Qian (Frontiers in Earth Science, 2024)
The Permian Capitanian-Changhsingian black shale formed in intra-platform basins are the major source rocks in Southwest China. However, the depositional conditions and organic matter accumulation of these black shales are not well understood. In this study, geochemical characteristics comprise TOC, major, trace and REEs from sixty-two samples from the studied outcrop in Northern Nanpanjiang Basin, Southwest China are systematically investigated to determine silicon source, paleo-ocean productivity, and paleo-redox conditions to reveal their influence on organic matter enrichment under 3rd-order sequence. The Capitanian-Changhsingian black shale in the study area is the result of the combined effects of active extensional activity, high paleo-productivity maintained by volcanic activity, and dysoxic and anoxic conditions represented by biological extinction events. There are differences in the factors controlling organic matter accumulation in black shale at different stages. The controlling factors for the organic enrichment during Capitanian (SQ2) are the rapidly deepening water mass of extensional rifts and the high productivity induced by volcanic ash in the igneous provinces, as well as the global anoxic event represented by "negative carbon isotope shift". The controlling factors during Changhsingian are the deepening of water mass under the reactivation of extensional rifts, resulting in a dysoxic environment, and the high productivity maintained by volcanic activity in South China. The Wuchiapingian black shale was formed under dysoxic conditions under the stagnation of extensional activity, and intermittent volcanic activity in South China maintained the high paleo-productivity level of the Wuchiapingian stage.